2020
DOI: 10.1038/s41598-020-63136-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface processing of the P1 adhesin of Mycoplasma pneumoniae identifies novel domains that bind host molecules

Abstract: Mycoplasma pneumoniae is a genome reduced pathogen and causative agent of community acquired pneumonia. The major cellular adhesin, P1, localises to the tip of the attachment organelle forming a complex with P40 and P90, two cleavage fragments derived by processing Mpn142, and other molecules with adhesive and mobility functions. LC-MS/MS analysis of M. pneumoniae M129 proteins derived from whole cell lysates and eluents from affinity matrices coupled with chemically diverse host molecules identified 22 proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 134 publications
1
29
0
Order By: Relevance
“…P1 adhesin of M. pneumoniae M129 is subject to extensive post-translational processing forming 22 proteo-forms, which are specific molecular forms of a protein product arising from a specific gene. Each of the proteo-forms retain the ability to bind to host molecules or their structural mimics and are surface accessible [ 31 ]. There are many issues that require further study, such as whether the antigen variations caused by post-translational modifications can affect the pathogenicity of M. pneumoniae .…”
Section: Virulence and Pathogenesis Of M Pneumoniaementioning
confidence: 99%
“…P1 adhesin of M. pneumoniae M129 is subject to extensive post-translational processing forming 22 proteo-forms, which are specific molecular forms of a protein product arising from a specific gene. Each of the proteo-forms retain the ability to bind to host molecules or their structural mimics and are surface accessible [ 31 ]. There are many issues that require further study, such as whether the antigen variations caused by post-translational modifications can affect the pathogenicity of M. pneumoniae .…”
Section: Virulence and Pathogenesis Of M Pneumoniaementioning
confidence: 99%
“…The most predominant adhesins in M. pneumoniae are P1 and P30 [17]. P1 is a remarkably versatile molecule that forms a complex with P30, P40, and P90; these colocalize to the tip of the terminal organelle to perform different functions, such as receptor recognition and gliding motility [4,18]. Schmitt et al has found that the P1 complex also contains P65, DnaK, C-terminal truncated forms of DnaK and P1, pyruvate dehydrogenase E1 α subunit (PDHA), HMW1, and HMW3 to coordinate the adherence of M. pneumoniae to host cells [4,19].…”
Section: Adhesins For Pathogenic Mycoplasmas In Humanmentioning
confidence: 99%
“…P1 is a remarkably versatile molecule that forms a complex with P30, P40, and P90; these colocalize to the tip of the terminal organelle to perform different functions, such as receptor recognition and gliding motility [4,18]. Schmitt et al has found that the P1 complex also contains P65, DnaK, C-terminal truncated forms of DnaK and P1, pyruvate dehydrogenase E1 α subunit (PDHA), HMW1, and HMW3 to coordinate the adherence of M. pneumoniae to host cells [4,19]. The P30 adhesin, originally regarded as an accessory protein, plays a role in localizing P1 to the terminal organelle and is involved in cell development [18]; the amino acid sequence of P30 holds substantial homology with some eukaryotic proteins in humans, indicating that P30 could be associated with the occurrence of certain autoimmune diseases [18].…”
Section: Adhesins For Pathogenic Mycoplasmas In Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct contact of M. hyopneumoniae cells with each other and with host cells or ECM molecules may render the pathogen capable of forming biofilms. Biofilm formation is a strategy used by many bacteria, including other mycoplasma species [112][113][114], to cope with host immune response or with antimicrobial effects, thereby rendering bacteria extremely adaptive and thus contributing to virulence. Recent studies have shown that at least some M. hyopneumoniae strains are indeed capable of forming biofilms, in experimental in vitro conditions, on abiotic surfaces or on host cell monolayers, and within the respiratory tract of experimentally infected swine [115,116].…”
Section: Hyopneumoniae Biofilm Formation Host Cell Invasion and Smentioning
confidence: 99%